Youth and Adult Education in the Context of Student Movements: The Cases of Egypt, Puerto Rico, and Chile - Maria A. Vetter; Mai Atta; Kamil M. Gerónimo-López; Javier M. Campos-Martínez; John D. Holst (Adult Education Research Conference, 2022)
Participants of the student movements in Egypt, Puerto Rico, and Chile present on their experiential learning in the context of the social movements that took place between 2005 and 2019.
Keywords: social movement learning; neoliberalism; student movements